What Is and Isn't in a Name. Issue 2 (31st July 2019) - Frumer, Yulia
Abstract: Although I remain sympathetic to the narrative behind the notion of "History of Knowledge, " I argue against redrawing the disciplinary boundaries around "knowledge, " as opposed to retaining the term "science." This is not because I think there is no place for a "history of knowledge, " and not because I am concerned that such a redrawing of disciplinary boundaries would open the floodgates of "anything goes." Rather, I am doubtful that problems of demarcation and exclusion can be resolved solely by changing a name. I draw on my personal experience as an East Asianist to suggest that the challenges I faced trying to fit into the community of historians of science and technology would not have been solved by renaming the discipline. At the same time, I also argue that changes can and do happen without a change of name. And finally, I maintain that the word "science" has important connotations that we do not want to give up.